Education as a Value of Use, of Exchange, and of Sign: Do we Move Towards the Abyss? Globalization of the 21st Century - Gómez Navarro, Ángel (2021)
In this paper we present the functional connection that exists between the meaning of value of use, of exchange, and of sign with respect to an idea of education conceived only from the cultural logic of consumption and the historical process of mercantilist expansion that characterizes our current society and that favors individualism, practicality, mere competitiveness, and profit. Thus, the idea of mercantilist education seems not only to be considered as an exchange value, object or thing to be sold, associated with what it can be worth in the market, but also with the sign value or what it can mean for individuals with respect to their differentiation sociocultural and economic status, which can also be observed in some curricular plans that do not incorporate the subjects of humanities and social sciences that are key to the integral development of the human being, the formation of critical thinking, values and democracy.